Teacher Resilience During the Covid-19 Pandemic - Mutiah, Diana; Ramadhani, Sarah Putri (JURNAL PSIKOLOGI, 2024)
During the COVID-19 pandemic, all education units conducted online learning. Therefore, in order to successfully adapt to the new system, teachers needed to have resilience. This research aimed to examine the prediction of self-efficacy, coping strategies, and social support on teacher resilience during the COVID-19 pandemic. A total of 301 teachers in Jabodetabek, where they had online teaching experience and participated in this research. Data processing with multiple regression analysis resulted in a significant prediction of self-efficacy, coping strategy, and social support on teacher resilience during the COVID-19 pandemic, with a percentage of 55.2% and a significant value of 0.000 (p < 0.05).Keywords: Teacher Resilience, Self-Efficacy, Coping Strategies, Social Support, COVID-19 Pandemic